2009
DOI: 10.1021/nl803584u
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Control of Self-Catalyzed Indium Phosphide Nanowires, Nanocones, and Nanopillars

Abstract: The morphological phase diagram is reported for InP nanostructures grown on InP (111)B as a function of temperature and V/III ratio. Indium droplets were used as the catalyst and were generated in situ in the metalorganic vapor-phase epitaxy reactor. Three distinct nanostructures were observed: wires, cones, and pillars. It is proposed that the shape depends on the relative rates of indium phosphide deposition via the vapor-liquid-solid (VLS) and vapor-phase epitaxy (VPE) processes. The rate of VLS is relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
74
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(81 citation statements)
references
References 46 publications
7
74
0
Order By: Relevance
“…Transition metals and group III metal particles for self-catalyzed nanowire growth are promising candidates. On the latter a lot of research is ongoing [5][6][7]. The former, including Cu and Al, have served as seed particle materials for Si and Ge nanowires with good results, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Transition metals and group III metal particles for self-catalyzed nanowire growth are promising candidates. On the latter a lot of research is ongoing [5][6][7]. The former, including Cu and Al, have served as seed particle materials for Si and Ge nanowires with good results, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The pillars are short and fat due to the relatively high growth temperature. This shape can be explained by the competition between two growth mechanisms: vapor-liquidsolid (VLS), which occurs primarily in the vertical direction; and vapor phase epitaxy (VPE), which occurs mainly in the lateral direction [27]. According to our previous study, the VPE rate increases relative to the VLS rate as one raises the substrate temperature.…”
Section: Experimental Methodsmentioning
confidence: 90%
“…Relatively few publications have considered self-catalysis of III/V nanowires using group III liquid droplets. In our group, we have shown that InP nanowires, nanocones, and nanopillars can be grown using indium droplets on InP(1 1 1)B by precisely controlling the growth temperature and V/III ratio [27].…”
Section: Introductionmentioning
confidence: 99%
“…InP is a direct band-gap semiconductor and has a bulk band-gap energy of 1.35 eV. Many groups have spent considerable time and effort on the solution phase synthesis of InP nanoparticles using diverse methods such as a dehalosilylation reaction method or a hot injection technique [17][18][19][20]. However, InP nanocrystals synthesized in organic solutions show quite low band-edge photoluminescence due to surface traps, dangling bonds, stacking faults, and a high activation barrier for carrier detrapping [21][22][23].…”
Section: Introductionmentioning
confidence: 99%